Influence of Plant Spacing, Seed Rhizome Size and Tree Canopy Environment on the Incidence of Rhizome Rot in Ginger - TABIN, T.; BALASUBRAMANIAN, D.; ARUNACHALAM, A. (Indian Journal of Hill Farming, 2015)
Rhizome rot disease is one of the major production constraints of ginger cultivation in hill agroecological region of Arunachal Pradesh. Considering both lower percentage disease incidence and higher yield, attempts have been made with different trials to overcome. Plant spacing of 20×20 cm and 25×25 was found to be optimum for disease incidence (46.2 & 41.7 %) and crop yield (45.1 & 47.9 t/ha) in the region. Disease incidence was high in close spacing of 10×10 cm (55.3 %) and low in more spacing of 35×35 cm (34.6 %). seed rhizome size of 60 to 80 g was found to be optimum for ginger planting. The smallest rhizome size used for seed had better growth performance than mother rhizome which had an additive effect on incidence of rhizome rot of ginger. Ginger grown under two canopy environment showed higher growth performance and lower disease incidence than that of field environment. The lowest disease incidence (22.2 %) with highest yield (48.4 t/ha) of ginger was recorded in silvi-canopy environment, while highest disease incidence (40.3 %) with lowest yield (35.2 t/ha) was recorded in open field conditions.